The Adoption of Total Productive Maintenance (TPM) Concept for Maintenance Procurement of Green Buildings in Malaysia - Zolkafli @ Zulkifly, Umi Kalsum; Zakaria, Norhanim; Mohd Danuri, Mohd Suhaimi (International Journal of Sustainable Construction Engineering and Technology, 2021)
Green building practices play an important role in achieving sustainability, especially in the construction industry. Green buildings are built to minimise the impact on the environment while reducing the impact of the building on the occupants. Unfortunately, the focus is on building green rather than in its maintenance. Correspondingly, Total Productive Maintenance (TPM) is a tool that has been promoted for its simplicity and the advantages of maintaining a delivery system. It assures the maintenance effectiveness of each industry, such as improving project quality, reducing waste, reducing production costs, increasing hardware accessibility and enhancing organisational support conditions. Meanwhile, procurement is considered to be the key to strengthen the maintenance operation of the construction industry. This study adopts the TPM concept for the maintenance of green buildings in Malaysia and aims to present the TPM concept for the maintenance of green buildings, and to establish the best procurement to adopt TPM for the maintenance of green buildings in Malaysia. This study has employed a qualitative approach where face-to-face and telephone interviews have been adopted. Interviews have been conducted with seven prominent respondents who possess more than 5 years of experience in green building maintenance. Content and thematic analyses have been used to analyse the data that are collected from the interviews; findings show that most of the respondents agreed that TPM could be adopted in the maintenance of green buildings. It has also been identified that for a public project the most appropriate procurement method is the facilities management contract whereas for private project the most popular procurements for green building maintenance are the lump sum contract, out-tasking contract and term contract. The results of this study provide practitioners with a new insight into the impromptu creation of a total productive maintenance concept that could improve the current building maintenance sector.